Influence of Mates Virginity on Black Soldier Fly, Hermetia illucens L. (Diptera: stratiomyidae) Mating Performance - Agus Dana Permana; Lulu Lusianti Fitri; Ucu Julita (Jurnal Biodjati, 2020)
Hermetia illucens (L.), the black soldier fly (BSF), has raised attention due to its potential in solving various organic waste prob-lems and the benefits of the prepupa biomass as an alternative highly nutritious livestock feed. The availability of BSF populations strongly depends on mating success and reproduction. The mechanism of sex-ual selection during the mating period also determines the success rate of mating and reproduction and the survivorship of the offspring. Here, we analyzed how the influence of different mating status (virgin-ity) of mating pairs on mating success, daily oviposition, the number of eggs and fertility of eggs. BSF reared in semi-outdoor screen cages with five replication and four treatment of mates virginity combina-tion. An analysis of variance (ANOVA) was used to assess differences in mating and reproductive performance among treatment. Male and female BSF performed the remating activity. The virginity of males and females significantly influenced mating and oviposition frequen-cy. Mate choice was influenced by the virginity of mates. However, vir-ginity status of mates did not affect the number of eggs, eggs weight, and eggs fertility. Understanding of mate selection behavior in rela-tion to virginity in BSF served as important information to obtain the sustain population in the various scale of rearing design applicat